In vitro application of proline in potato tubers under newly emerging bacteria Lelliottia amnigena infection. (May 2023) - Osei, Richard; Boamah, Solomon; Boakye, Thomas Afriyie; Wei, Lijuan; Jin, Mengjun; Gyasi Santo, Kwadwo; Takyi, Isaac; Yang, Chengde
Abstract: Biotic stress deleteriously affects growth, development, and productivity in plants. Proline (Pro) plays a significant role in enhancing plant resistance to pathogen infection. However, its effects on reducing Lelliottia amnigena -induced oxidative stress in potato tubers remain unknown. The present study aims to evaluate the in vitro Pro treatment in potato tubers exposed to a newly emerging bacterium, L. amnigena . Sterilized healthy potato tubers were inoculated with 0.3 mL of L. amnigena suspension (3.69 × 10 7 CFU mL −1 ) 24 h before Pro (5.0 mM) application. The L. amnigena treatment significantly increased the contents of malondialdehyde (MDA) and hydrogen peroxide (H2 O2 ) in the potato tubers by 80.6 and 85.6%, respectively, compared to the control. Application of proline (Pro) decreased MDA and H2 O2 contents by 53.6 and 55.9%, respectively, compared to the control. Application of Pro to L. amnigena -stressed potato tubers increased the activities of NADPH oxidase (NOX), superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), polyphenol oxidase (PPO), phenylalanine ammonia-lyase (PAL), cinnamyl alcohol dehydrogenase (CAD), 4-coumaryl-CoA ligase (4CL) and cinnamate-4-hydroxylase (C4H) C4H by 94.2, 96.3, 97.3, 97.1, 96.6, 79.3, 96.4, 93.6, and 96.2%, respectively, compared to the control. In comparison to the control, the genes PAL, SOD, CAT, POD, and NOX were significantly increased in the Pro-treated tubers at 5.0 mM concentration. Tubers treated with Pro + L. amnigena increased the transcript levels of PAL, SOD, CAT, POD, and NOX by 2.3, 2.2, 2.3, 2.5, and 2.8-fold respectively, compared to the control. Our findings suggested that pretreatment of tubers with Pro might reduce lipid peroxidation and oxidative stress by enhancing enzymatic antioxidant activity and gene expression.